2023
DOI: 10.18280/ijht.410113
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Orientation of Non-Tracking Solar Applications in Baghdad City

Abstract: This study presents a solution to the selection of the optimum orientation for non-tracking solar photovoltaic panels and non-tracking solar thermal collectors with a new methodology in Baghdad city. The optimum tilt angle of solar application was determined monthly, seasonal and yearly based on the largest monthly average daily total solar radiation incident on the surface in Baghdad. The solar radiation and tilt angle were calculated theoretically with the help of MATLAB R2016b and the theoretical data of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It was also observed that the best insolation was on April 26, where the curve takes a stable and symmetrical behavior around noon, and this corresponds when the azimuth angle is zero (towards the south). 43 In addition to that, values close to the optimum values were recorded, 43 because the weather on that day was very clear, with little clouds and dust. The intensity of solar radiation directly affects the performance of all solar applications, including SBCs.…”
Section: Load Testsmentioning
confidence: 75%
See 1 more Smart Citation
“…It was also observed that the best insolation was on April 26, where the curve takes a stable and symmetrical behavior around noon, and this corresponds when the azimuth angle is zero (towards the south). 43 In addition to that, values close to the optimum values were recorded, 43 because the weather on that day was very clear, with little clouds and dust. The intensity of solar radiation directly affects the performance of all solar applications, including SBCs.…”
Section: Load Testsmentioning
confidence: 75%
“…The dimensions of the base are 42.2 cm * 42.2 cm and the height changes from 19 to 44 cm, so that the box is tilted from the top at an angle of 35°, this angle is almost the optimum annual tilt angle for Baghdad city. 43 The box from the inside is made of aluminum alloy sheets with a thickness of 0.8 mm. The dimensions of the base are 35 cm * 35 cm and the height changes from 15 to 39 cm, therefore it is inclined at the same angle as the inclination of the box.…”
Section: Methodsmentioning
confidence: 99%